ANALYSIS OF CHEMOTHERAPY COSTS IN BREAST CANCER PATIENTS PARTICIPATING BPJS AT DHARMAIS CANCER HOSPITAL JAKARTA - Piter Piter; Rangki Astiani; Kristin Monica; Yuri Permatasari (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to find out how much chemotherapy costs for inpatient breast cancer chemotherapy patients participating in BPJS and whether there is a difference in real hospital costs compared to INA-CBGs rates. This research is a descriptive, observational study taken from secondary data, in the form of medical record data, laboratory data, INA-CBGs e-claim data and financial data on patient medical costs in accordance with the inclusion and exclusion criteria totaling 100 patient data. Data analysis uses One Sample T-test to see whether there is a significant difference between real costs and INA-CBGs rates. Based on the results of the One Sample T-test, it shows that there is a significant difference. According to the statistical results, a significance of p<0.005 was obtained in class 3 and there was no significant difference in class 1 or class 2. The average cost that breast cancer patients have to pay for each procedure chemotherapy, severity level I Rp. 7,129,348, severity level II Rp. 9,323,275 and severity level III Rp. 9,037,426.